2007
DOI: 10.1159/000109817
|View full text |Cite
|
Sign up to set email alerts
|

Does Glucose in Dialysis Fluid Protect Erythrocytes in Patients with Chronic Renal Failure?

Abstract: Background/Aims: The aim of this study was to assess the multifaceted influence of glucose present in dialyzing fluid on erythrocytes of patients with chronic renal failure (CRF) undergoing regular hemodialysis. Methods: A group of 44 subjects with CRF undergoing regular hemodialysis was studied. Two tests were used: osmotic fragility and resistance to the hemolytic agent saponin. The total content of isoprostane 8-iso-prostaglandin F2α type III (8-iPF2α-III) in plasma and erythrocyte’s m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 59 publications
0
19
0
1
Order By: Relevance
“…Other authors also showed that the activity of G6PDH depends on the glucose content in the dialysate. The activity was the highest in the presence of glucose [41,42,43]. …”
Section: Discussionmentioning
confidence: 99%
“…Other authors also showed that the activity of G6PDH depends on the glucose content in the dialysate. The activity was the highest in the presence of glucose [41,42,43]. …”
Section: Discussionmentioning
confidence: 99%
“…Serial studies from Dolegowska's group have focused on the role of glucose and the protective effects of erythrocytes on oxidative stress in the HD population [7][8][9][10] . In this issue [11] , they demonstrated further that glucose present in dialysate could conserve erythrocyte membrane integrity and limit possible hemolysis induced by the HD process. Such observations may bring high clinical implications and deserve further discussions.…”
mentioning
confidence: 91%
“…The HMP pathway can provide reducing equivalents and actively increase antioxidant glutathione (GSH) synthesis during HD therapy. Therefore, the risk of hemolysis induced by HD can be reduced by adding glucose in dialysis fluid [11] . However, superoxide production during hypoglycemic status is primarily by NADPH oxidase [15] .…”
mentioning
confidence: 99%
See 2 more Smart Citations